أثر الإبداع الإداري على الأداء التنظيمي: الثقافة التنظيمية كمتغير وسيط دراسة حالة مدارس محافظة شمال الشرقية في سلطنة عمان - خالد محمد عدي البطاشي
This study discussed the effect of organizational culture as a mediating factor on the relationship between administrative creativity behavior and organizational performance. From the point of view of workers in the schools of the North Al Sharqiyah Governorate in the Sultanate of Oman, and from this standpoint, the study aimed to identify the impact of administrative creativity on organizational performance using organizational culture in the schools of the North Al Sharqiyah Governorate in the Sultanate of Oman. To achieve this; The analytical descriptive approach was used for its suitability for this study, and a questionnaire consisting of (54) items was developed and distributed on the dimensions of the main axes represented in: administrative creativity, organizational culture, and organizational performance. The study population consists of workers in schools in the North Al Sharqiyah Governorate in the Sultanate of Oman. The number of them is (550) workers, and the study sample was (226), and the study followed the method of a non-stratified random sample in the schools of the North Al Sharqiyah Governorate in the Sultanate of Oman. To use the Structural Equation Modeling Method (SMART PLS), the third edition, and the results of the study showed that there is a direct positive relationship between administrative creativity and organizational performance in the schools of Al Sharqiyah North Governorate in the Sultanate of Oman, and there is a direct positive relationship between administrative creativity and organizational culture, as well as there is a relationship Direct positive relationship between organizational culture and organizational performance. Where the P-value was less than (5%), the path coefficient was (2.310), and the T-coefficient was (1.717). There is also an effect of organizational culture on the relationship between administrative creativity and organizational performance in North Sharqiya schools in the Sultanate of Oman. Where the P-value coefficient was less than (5%), the path coefficient was (3.150), and the T coefficient was (18.129). The study revealed that there is a direct statistical relationship between organizational culture and organizational performance, where the P-value coefficient was less than (5%). and achieved the path coefficient (1.350) as well as the T coefficient (13.150), and the study recommended the need to work on expanding the application of administrative creativity in higher education institutions in the Sultanate of Oman. The study contributed to identifying the theoretical framework of organizational culture and administrative creativity, as the study theoretically contributed to identifying the theory of organizational performance, as well as the study contributed practically to measuring the study model and identifying the direct impact of the study variables administrative creativity on organizational performance and identifying the indirect impact of organizational culture in the relationship Between Administrative Creativity and Organizational Performance in Al Sharqiyah North Governorate, Sultanate of Oman.